Efficacious Technology Management A Guide for School Leaders - Ackerman, Gary (Open textbook library., 2018)
Dr. Gary Ackerman, an educational technology specialist with decades of experience in K-12, community college, and faculty development has released Efficacious Technology Management: A Guide for School Leaders. This is his second book, and it is available under a Creative Commons license.